Increased von Willebrand factor, P-selectin and fibrin content in occlusive thrombus resistant to lytic therapy - Sambola, Antonia; Del Blanco, Bruno García; Ruiz-Meana, Marisol; Francisco, Jaume; Barrabés, José A.; Figueras, Jaume; Bañeras, Jordi; Otaegui, Imanol; Rojas, Angeles; Vilardosa, Úrsula; Montaner, Joan; García-Dorado, David (Thrombosis and Haemostasis, 2016)
Therapeutic fibrinolysis is ineffective in 40 % of ST-segment elevation acute myocardial infarction (STEMI) patients, but understanding of the mechanisms is incomplete. It was our aim to compare the composition of coronary thrombus in lysis-resistant STEMI patients with that of lysis-sensitive patients. Intracoronary thrombi (n=64) were obtained by aspiration in consecutive STEMI patients. Of them, 20 had received fibrinolysis and underwent rescue percutaneous coronary intervention (r-PCI, lysis-resistant patients) and 44 underwent primary PCI (p-PCI). Lysis-sensitivity was determined in vitro by clot permeability measurements and turbidimetric lysis in plasma of 44 patients undergoing p-PCI and 20 healthy donors. Clot-lysis sensitivity was defined as a clot-lysis time not greater than 1 SD over the mean of healthy donors. Coronary thrombus composition in 20 lysis-resistant and in 20 lysissensitive patients was analysed by immunofluorescence with confocal microscopy. Plasma biomarkers (P-selectin, VWF, PAI-1, t-PA, D-dimer, TF pathway markers, plasmin and CD34+) were measured simultaneously on peripheral blood. Lysis-resistant clots had higher levels of fibrin (p=0.02), P-selectin (p=0.03) and VWF (p=0.01) than lysis-sensitive clots. Among thrombi obtained ≤ 6 hours after onset of symptoms, those from lysis-resistant patients showed a higher content in fibrin than those from p-PCI patients (p=0.01). Plasma PAI-1 (p=0.02) and D-dimer levels were significantly higher (p=0.003) in lysis-resistant patients, whereas plasmin levels were lower (p=0.03). Multivariate analysis showed the content of fibrin and VWF within thrombus as predictors of thrombolysis resistance. In conclusion, coronary thrombi in STEMI patients resistant to fibrinolysis are characterised by higher fibrin, P-selectin and VWF content than lysis-sensitive thrombi.
Keywords: Clot structure; coronary syndrome; fibrin; fibrinolytic disorders; von Willebrand factor